1976
DOI: 10.1111/j.1365-2222.1976.tb01918.x
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal steroid aerosol in perennial rhinitis: comparison with an antihistamine compound

Abstract: Summary Intranasal betamethasone valerate aerosol, given for 28 days, was compared with an oral antihistamine compound in a double‐blind, double‐dummy, cross‐over trial involving thirty patients with perennial rhinitis. The steroid aerosol was more effective in reducing symptoms and was preferred by the patients (P < 0·01). Nasal blockage index, calculated from oral and nasal peak expiratory flow measurements, did not provide useful or additional information. There were no side effects from the steroid and Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Evaluation of the data separately at each provocation step by Mests both with and without correction for baseline difl"erences gave similar results. Symptom score data were evaluated separately (Mests) at each provocation step: 10, 100, 1000, and 10000SQ-U/ml(runs7, 9,11,13) for the four score variables: itch, sneeze, secretion, and blockage ( Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of the data separately at each provocation step by Mests both with and without correction for baseline difl"erences gave similar results. Symptom score data were evaluated separately (Mests) at each provocation step: 10, 100, 1000, and 10000SQ-U/ml(runs7, 9,11,13) for the four score variables: itch, sneeze, secretion, and blockage ( Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Only a few comparisons have been made between steroids and the new nonsedating antihistamines on blockage in hay fever (8,9,21), and although steroids are advocated in case of blockage instead of antihistamines (12,16), we find that further study by acoustic rhinometry, a more recent objective method for evaluation of nasal patency, is justified.…”
mentioning
confidence: 92%
“…Reasons for exclusion were use of: non-random allocation, 28 29 a single blind protocol, 30 31 combined intranasal corticosteroid and oral antihistamines in the comparison arm, 32 33 topical antihistamines in the comparison arm, 34 35 decongestant in the comparison arm,3638 non-clinical challenge or outcome, 39 40 and the publication of an abstract only without reporting detailed results 41 – 43…”
Section: Methodsmentioning
confidence: 99%
“…In comparison with antihistamines, one study has shown equal efficacy on nasal symptoms (192), while seven double-blind studies have demonstrated the GCS spray to be more effective, especially for nasal blockage (17,25,57,65,78,104,150).…”
Section: Comparison With Other Treatmentsmentioning
confidence: 99%